1975
DOI: 10.1128/iai.12.2.433-436.1975
|View full text |Cite
|
Sign up to set email alerts
|

Changes in buoyant density relationships of two cell types of Coxiella burneti phase I

Abstract: Coxiella burneti phase I, purified from a formalin-inactivated yolk-sac vaccine, was separated into two bands of morphologically distinct cell types when subjected to sucrose gradient centrifugation. Recycling of the less dense, rod-shaped cells in unbuffered sucrose gradients (pH 5.5 to 6.0) resulted in the formation of bands having the location and appearance of the original two bands. Recycling of the denser band of larger ovoid-shaped cells yielded a single band, suggesting that the larger cell type arose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1976
1976
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Although we cannot directly rule out the possibility that there is a complex cycle in the multiplication of C. burnetii, our data do not support it. Other investigators have observed two morphological types of phase I or II C. burnetii after purification by density gradient centrifugation (9,28,29). Wiebe et al (29) speculated that the oval to round forms may be degenerate forms produced by host-mediated digestion or alteration by chemical treatment :o .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we cannot directly rule out the possibility that there is a complex cycle in the multiplication of C. burnetii, our data do not support it. Other investigators have observed two morphological types of phase I or II C. burnetii after purification by density gradient centrifugation (9,28,29). Wiebe et al (29) speculated that the oval to round forms may be degenerate forms produced by host-mediated digestion or alteration by chemical treatment :o .…”
Section: Resultsmentioning
confidence: 99%
“…5 ,tm. or that they may represent two stages in a complex developmental cycle. Wachter et al (28) indicated that the larger forms could be derived from the rod-shaped rickettsiae by various stresses.…”
Section: Resultsmentioning
confidence: 99%
“…burnetii displays a complex intracellular cycle, leading to the formation of spore-like forms (227). McCaul and Williams (228) have proposed the terms "small-cell variant" (SCV) and "large-cell variant" (LCV) to differentiate the two C. burnetii cell forms observed in persistently infected cells (48,251,388,398). SCVs and LCVs correspond to different intracellular development stages of C. burnetii (227).…”
Section: Intracellular Cycle and Sporulation-like Processmentioning
confidence: 99%
“…The experiments reported here do pertain to reports of heterogeneous rickettsial banding in CsCl gradients, however. C. burnetii in phase I gave rise in two bands in CsCl (22), and inactivation with Formalin (18,19,22) or ultraviolet light (18, 19) caused a shift of organisms from the light to the heavy band. (It also has been reported that lengthy centrifugation of C. burnetii at lowered pH in sucrose caused the appearance of a heavy band, but that ultraviolet light or Formalin treatment, which caused heavy band formation in CsCl, did not have that effect in sucrose [18]).…”
Section: Discussionmentioning
confidence: 99%
“…C. burnetii in phase I gave rise in two bands in CsCl (22), and inactivation with Formalin (18,19,22) or ultraviolet light (18, 19) caused a shift of organisms from the light to the heavy band. (It also has been reported that lengthy centrifugation of C. burnetii at lowered pH in sucrose caused the appearance of a heavy band, but that ultraviolet light or Formalin treatment, which caused heavy band formation in CsCl, did not have that effect in sucrose [18]). Noninactivated phase I C. burnetii which naturally formed two bands in CsCl also were easily distinguished morphologically, the rickettsiae in the upper band being smaller with more condensed nucleoids than those in the lower band (22).…”
Section: Discussionmentioning
confidence: 99%